Thyrotoxicosis and Risk of Cognitive Disorders in Older Adults at a Tertiary Care Centre in Pakistan (Medical Forum Monthly, 2024)
Objective: To ascertain whether there's a heightened risk of cognitive disorders linked to both endogenous and exogenous causes of thyrotoxicosis. Study Design: Case control, Cohort study Place and Duration of Study: This study was conducted at the Department of Medicine at Nishtar hospital, Multan, from March 2021 to February 2022.Methods: Two hundred and ten patients were enrolled and divided into case group (105) and control group (105). The clock drawing test and Mini Mental State Examination was used for evaluation of cognitive function, both administered by a single observer. Subjects included in the study had received a minimum of primary education or higher and were above the age of 65 years.Results: Regarding thyrotoxicosis, 53.3% patients were exogenous, 15.7% was endogenous and 31.0% patients was unknown thyrotoxicosis. Exogenous 68.5% was most common in cases as compare to the controls 48.1%. In this study MMSE (25-30) score was 65.7% in cases and 85.7% in controls. Status of cognitive impairment evaluated by clock drawing test 32.4% in cases and 20.0% in controls.Conclusion: The prevalence of cognitive impairment was notably elevated in individuals with thyrotoxicosis, whether endogenous or exogenous, compared to control subjects. Additionally, the presence of cognitive impairment exhibited a correlation with the level of thyroid-stimulating hormone (TSH), with cognitive function declining as TSH levels increased.